Research in Pesantren-based Higher Education: Exploring The Factors Improving Lecture's Research Performace - Abdu Alifah; M. Syamsul Maarif; I Made Sumertajaya (STAI Hubbulwathan Duri, 2022)
Integrating two different systems between higher education and pesantren (Islamic boarding schools), Pesantren-based Higher Education (PTBP) is alleged as an ideal Islamic higher education model considering its critical role in the process of integration-interconnection of science and Islamic teaching. Like other Islamic higher educations in Indonesia, PTBP represents poor organizational performance, particularly in research productivity and quality. Since research performance has the most considerable portion in the higher education performance evaluation both nationally and internationally, this study attempted to explore the factors that possibly improve lecturers' research performance at PTBP, categorized into the level of the individual, institutional and resource factors. This study involved 84 lecturers at 7 PTBP in Bogor, Indonesia, selected based on the stratified random sampling and voluntary sampling method. The collected data was analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that only research competence positively affected research performance at the individual level, but not for work motivation and time management. Research culture and academic leadership insignificantly affected research performance. However, only high-performance work practice (HPWP) at the institutional level positively affected research performance. Meanwhile, collaboration networks at the resource level positively affected research performance, but not for university research funding. The managerial implications are further discussed in this study.